ANALYSIS OF THE KINDERGARTEN PEDAGOGIES IN LOWLAND SCHOOLS IN MARINDUQUE: BASIS FOR KINDERGARTEN TEACHERS’ DEVELOPMENT PROGRAM - Romasanta, Norman (International Journal of Arts, Sciences and Education, 2023)
This study analyzes pedagogies used by Kindergarten teachers in 19 lowland schools in Torrijos, Schools Division of Marinduque. Data was collected through a survey questionnaire, observation tool, and interviews with 21 participants. The researcher-made observation tool was validated among 30 other districts, showing a Cronbach's alpha of 0.932. The study found that teachers with a mean of 11.52 years in service teach Kindergarten and 61.9% specializing in Early Childhood Education. The overall mean is 4.4476, with a 0.3516 standard deviation. 46.62% attended Division Training Workshops on the National Kindergarten Curriculum, 42.86% attended National Webinars on Kindergarten Remote Teaching and Learning, and 28.57% attended Division Enhancement Training Workshops for Kindergarten Teachers. Kindergarten pedagogies have no significant relationship with identified profiles. The study found that most teachers in lowland schools are experienced, with over half specialized in Early Childhood Education. Most teachers handle 21-50 learners, with some handling 20 or fewer. All teachers follow pedagogies based on D.O no. 47, s. 2016 and D.O no. 42, s. 2017. Training is limited to some teachers, and an upskilling program is needed to improve the execution of pedagogies in teaching Kindergarten programs. This study recommends proper orientation for new kindergarten teachers, including instructional delivery and planning. The Department of Education should continue skill enhancement to teachers with other specializations. The number of learners handled by teachers should be considered. Pedagogies in teaching the Kindergarten program are vital thus, the Department should design training and development activities to update professional practice in the Kindergarten program.